Nasal lymphatic obstruction of CSF drainage as a possible cause of Alzheimer’s disease and dementia - Phillips, William Thomas; Schwartz, Joyce Gensberg (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease, the most common form of dementia among older adults, slowly destroys memory and thinking skills. In recent years, scientists have made tremendous progress in understanding Alzheimer's disease, still, they don't yet fully understand what causes the disease. This article proposes a novel etiology for Alzheimer's disease. Our hypothesis developed from a review of nuclear medicine scans, in which the authors observed a significant increase in nasal turbinate vasodilation and blood pooling in patients with hypertension, sleep apnea, diabetes and/or obesity, all risk factors for Alzheimer's disease. The authors propose that nasal turbinate vasodilation and resultant blood pooling lead to the obstruction of normal nasal lymphatic clearance of cerebrospinal fluid and its waste products from the brain. The nasal turbinate vasodilation, due to increased parasympathetic activity, occurs alongside the well-established increased sympathetic activity of the cardiovascular system as seen in patients with hypertension.The increased parasympathetic activity is likely due to an autonomic imbalance secondary to the increase in worldwide consumption of highly processed food associated with dysregulation of the glucose regulatory system.The authors' hypothesis offers a novel mechanism and a new paradigm for the etiology of Alzheimer's disease and helps explain the rapid worldwide rise in the disease and other dementias which are expected to double in the next 20 years. This new paradigm provides compelling evidence for the modulation of the parasympathetic nervous system as a novel treatment strategy for Alzheimer's disease and other degenerative brain diseases, specifically targeting nasal turbinate lymphatic flow.